Procedures concluded to erosion geomorphological characteristics of Naxos, Mykonos, Tinos Islands (Aegean Sea). - Evelpidou, N.; Leonidopoulou, D.; Vassilopoulos, A.; Stournaras, G. (7th Panhellenic European Hydrogeology Conference, 2005)
In this paper the study of geomorphological characteristics, developed because of the run off, in the Cyclades area and especially in Tinos, Mykonos and Naxos islands, has taken place. In order to explain their development, the geomorphological characteristics were correlated with the lithological, tectonical and hydrological characteristics of the study area. The study area is characterized by a wide variety of different lithological and hydrogeological factors. To achieve this study’s targets, GIS and GPS technology was used in order to geographically and statistically analyse the morphological, hydrological, lithological and tectonic factors of this area. The main sources were the pre-existent maps and the literature, aerial photos and satellite images, while the extensive field work resulted to the geomorphological mapping of the area. The results of this study are related to the analysis of the current morphology and are presented on maps and rodograms.